KARAKTERISTIK PASIEN KALAZION DI RUMAH SAKIT ISLAM SITI RAHMAH KOTA PADANG TAHUN 2022-2024 - Nabila, Daffa Hartia; Ashan, Haves; Birman, Yuliza (Nusantara Hasana Journal, 2025)
Background: Chalazion is one of the eye diseases that often presents as a mass lesion on the eyelid. This occurs due to the obstruction of sebaceous secretion from the meibomian or zeis glands. Chalazion can occur at any age, including in children. Objective: To identify the characteristics of Chalazion patients at RSI Siti Rahmah in Padang City from 2022 to 2024. Method: All patients diagnosed with chalazion at RSI Siti Rahmah, Padang City. This study was conducted using a descriptive categorical method, utilizing secondary data. The sample size in this study was 51, using total sampling techniques. Results: The most common chalazion patients were aged 21-30 years (47.1%). The majority of the subjects were female (62.7%). The most common location was on the upper eyelid (76.5%). The most widely used management was medication (62.7%). Conclusion: Chalazion patients predominantly occur in the age group of 21-30 years, are mostly female, often located on the upper eyelid, and medication management.